Meta Analisis: Efektifitas Pembelajaran Blended Learning terhadap Intelegensi Pasca Pandemi COVID-19 - Rifelino, Rifelino; Syahri, Budi; Jalinus, Nizwardi; Abdullah, Rijal (Asatiza: Jurnal Pendidikan, 2023)
The aim of the study is to reveal the effectiveness of blended learning on students' intelligence and behavior during the situation of Covid-19 pandemic. The data source for this type of meta-analyst research analysis comes from 25 articles published in indexed journals. Sampling using purposive sampling technique. The collection of these journals is related to the discussion of blended learning and intelligence after the learning process takes place. Data analysis uses quantitative data by considering the effect size. The results revealed that the application of blended learning contributed to increasing students' intelligence. This is supported by the curiosity of students in utilizing information technology in the learning process.